2018
DOI: 10.26582/k.50.2.5
|View full text |Cite
|
Sign up to set email alerts
|

Inside game effectiveness in NBA basketball

Abstract: The inside game constitutes an essential aspect of modern basketball, particularly in the National Basketball Association (NBA), in where the best players of the world compete. The purpose of this study was to identify players' dynamics that increase game performance when using inside pass in the NBA, considering game contextual effects. The sample included 808 inside passes from 25 randomly selected matches of the 2011 NBA Playoffs series. A series of logistic regression analyses were used to analyse passers … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 30 publications
(47 reference statements)
0
11
0
Order By: Relevance
“…Previously, winning teams were reported to be more disciplined when performing collective tactical actions (i.e., teamwork) during both short and long attacks (i.e., increasing scoring opportunities) [31]. The current results can provide further basis for these group-tactical behaviours that lead to open 3-point shots during set plays and transitions (e.g., match pace variations and inside-outside passes), and easy scoring during fast breaks (e.g., quick actions after defensive rebounds) [32][33][34].…”
Section: Discussionmentioning
confidence: 77%
“…Previously, winning teams were reported to be more disciplined when performing collective tactical actions (i.e., teamwork) during both short and long attacks (i.e., increasing scoring opportunities) [31]. The current results can provide further basis for these group-tactical behaviours that lead to open 3-point shots during set plays and transitions (e.g., match pace variations and inside-outside passes), and easy scoring during fast breaks (e.g., quick actions after defensive rebounds) [32][33][34].…”
Section: Discussionmentioning
confidence: 77%
“…Besides scoring points, they significantly reduce the opponent's chance to create a quick and favorable transition. A regained possession of the ball logically increases a shot opportunity for the offense [15,16,38].…”
Section: Most Efficient Ends Of the Ball Possessionmentioning
confidence: 99%
“…The collective behaviour of players for the inside pass events was analysed in [8], where it was shown that the interactions combining passer's previous actions (dribbling or faking) with receiver's cuts towards the basket achieved the highest offensive effectiveness. Performing screens in favour to the receiver was an effective alternative to increase inside passing options since it reduces the defensive [8]. The effect of space among players towards team performance is analysed in [26].…”
Section: Data Driven Performance Analysis In Basketballmentioning
confidence: 99%
“…In the past, researchers have predominantly used two types of data to analyse basketball game strategies, i.e., play-by-play data that describe different events that happen on court such as shots, passes, dribbles, and fouls and player and ball tracking data. For example, play-by-play data can be used to learn the effectiveness of different types of PNR plays [7], or the factors that influence the effectiveness of inside-passes [8]. Wu and Swartz [9] proposed corrections for substitution errors using logistic classification models based on play-by-play data obtained from the National Basketball Association (NBA), in the USA.…”
Section: Introductionmentioning
confidence: 99%